Reassessing the Role for Lamivudine in Chronic Hepatitis B Infection: A Four-Year Cohort Analysis - Tahir Shaikh; Curtis Cooper (Canadian Journal of Gastroenterology)
The data supporting the use of antiviral agents other than lamivudine in the management of patients with hepatitis B virus (HBV) infection are based on highly selected clinical trial populations that may not be representative of typical HBV-infected populations encountered in many clinics. Despite its limitations, however, lamivudine is relatively inexpensive and widely available and, in carefully selected patients, can still be successfully used to achieve long-term HBV suppression. This study investigated the long-term effectiveness of lamivudine in an adherent, frequently monitored, noninvestigational HBV-infected cohort.